Analisis Penawaran Jagung di Jawa Tengah - Setyowati Setyowati; Agustono Agustono; Marlisa Maharani (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This research aims to analyze some factors that influence the corn supply in Central Java, and to analyze the corn supply elasticity in Central Java. The basic method used in this research is descriptive method. The location of this research stated with purposive, that is Central Java Province. And the data used in this research is secondary data.